2022
DOI: 10.1097/scs.0000000000009106
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of Facial Palsy on Social Media Over the Last 5 Years

Abstract: Background: Social media (SoMe) has become a powerful platform for distributing health information. Facial palsy (FP) results in functional and social impairment and lowers quality of life. Social media may help to raise awareness of FP sequalae. This study aims to determine the FP information growth on SoMe platforms and parameters that influence user engagement on FP content. Methods: Five commonly used SoMe platforms (Facebook, Instagram, TikTok, Twitter, and Reddit) were analyzed. Data on 18 FP hashtags … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Our findings showed that age, gender, marital status, employment, nationality, education level, and the source of information about Bell's palsy were all significantly correlated with participants' awareness. Previous studies align with our findings by showing similar factors associated with awareness [ 10 , 12 , 14 ]. Alherabi et al [ 10 ] found that awareness increased with age; female participants had better awareness, and those who read books and magazines/book readers were more aware.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings showed that age, gender, marital status, employment, nationality, education level, and the source of information about Bell's palsy were all significantly correlated with participants' awareness. Previous studies align with our findings by showing similar factors associated with awareness [ 10 , 12 , 14 ]. Alherabi et al [ 10 ] found that awareness increased with age; female participants had better awareness, and those who read books and magazines/book readers were more aware.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings align with previous studies [ 13 ] showing family and friends as the source of information. Studies also highlighted the significance of social media in spreading Bell’s palsy information [ 14 , 15 ]. It was found that the use of reels (p<0.001) and the profile host by healthcare providers, interacting with their followers by liking (p<0.001), and replying (p<0.001) to comments increased engagement significantly in raising awareness about Bell’s palsy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation